2011
DOI: 10.1523/jneurosci.5981-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Anatomically Defined Neuron-Based Rescue of Neurodegenerative Niemann–Pick Type C Disorder

Abstract: Niemann-Pick type C disease is a fatal lysosomal storage disorder caused by loss of NPC1 function. The disorder severely affects multiple body systems, particularly the nervous system. To test whether rescue of NPC1 activity in neurons, astrocytes, or other cell types can correct the neurological defects, a Tet-inducible Npc1-YFP transgene was introduced into Npc1−/− mice for the cell type-specific rescue of NPC1 loss. NPC1-YFP produced in neurons prevented neuron degeneration, slowed reactive glial activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
122
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(136 citation statements)
references
References 56 publications
10
122
2
Order By: Relevance
“…The phenotype of these mice is similar to, but slightly less severe than, that of Npc1 Ϫ / Ϫ mice ( 26,75 ). More recently, NPC1 was eliminated specifi cally in certain cell types ( 76 ) and, reciprocally, was expressed only in specifi c cells of Npc1 Ϫ / Ϫ mice ( 77 ). These studies have been particularly useful for understanding in which cells of the brain loss of NPC function is the most detrimental (see Loss of NPC Function in Cells of the Brain).…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…The phenotype of these mice is similar to, but slightly less severe than, that of Npc1 Ϫ / Ϫ mice ( 26,75 ). More recently, NPC1 was eliminated specifi cally in certain cell types ( 76 ) and, reciprocally, was expressed only in specifi c cells of Npc1 Ϫ / Ϫ mice ( 77 ). These studies have been particularly useful for understanding in which cells of the brain loss of NPC function is the most detrimental (see Loss of NPC Function in Cells of the Brain).…”
mentioning
confidence: 74%
“…Furthermore, genetic deletion of NPC1 in astrocytes alone did not cause the neuropathology exhibited by Npc1 Ϫ / Ϫ mice ( 141 ). Nor did Tet-induced expression of NPC1 in astrocytes alone of Npc1 Ϫ / Ϫ mice slow disease progression, except for a small delay in weight loss ( 77 ). In contrast, one study reported that cholesterol storage was decreased, and survival of Npc1 Ϫ / Ϫ mice was increased, by expression of NPC1 in astrocytes under control of the glial fi brillary acidic protein promoter.…”
Section: Cyclodextrin As a Therapy For Npc Diseasementioning
confidence: 98%
See 2 more Smart Citations
“…18 In murine NPC models, intracellular storage of gangliosides occurs maximally in large pyramidal neurons, Purkinje cells in the cerebellum, and neurons in the lateral thalamus, hippocampus, and brain stem 6,19 ; and maximal neuronal loss occurs in the thalamus and cerebellum. [19][20][21] The earliest human neuropathologic studies showed that neuroaxonal dystrophy was maximal in the thalamus and cerebellum. 22 In humans, neuropathologic studies demonstrated that noncerebellar brain regions develop NFTs in the basal ganglia, thalamus, brain stem, cerebral cortex, and hippocampus.…”
Section: Discussionmentioning
confidence: 99%